Educational Robotics to Foster and Assess Social Relations in Students' Groups - Ponticorvo, Michela; Rubinacci, Franco; Marocco, Davide; Truglio, Federica; Miglino, Orazio (Frontiers in Robotics and AI, 2020)
Robotics has gained in recent years, an important role in education both in formal and informal contexts, mainly in the fields related to STEM. Indeed Educational Robotics (ER) can be fruitfully applied also to soft skills, as it allows to promote social links between students, if it is proposed as a group activity. Working in group to solve a problem or accomplish a task in the robotics field allows to foster new relations and overcome the constraints of the established links connected to the school context. Together with this aspect, ER offers an environment where it is possible to assess group dynamics by the means of sociometric tools. In this paper we will describe an example of how ER can be used to foster and assess social relations in students' group. In particular we compare three conditions: educational robotics lab, coding lab with Scratch and control group, proposed to Italian students of middle school. In order to analyze social relations among students, Moreno sociometric tools have been employed. Results indicate that educational robotics can effectively foster relations between students and, jointly with sociometric tools, can be employed to portrait group dynamics in a synthetic and manageable way.